Linear dicarboxylate-based pyridyl-appended cobalt(ii) coordination polymers in search of opto-electronic properties. (20th May 2020) - Ahmed, Faruk; Datta, Joydeep; Khan, Samim; Dutta, Basudeb; Islam, Sakhiul; Naaz, Sanobar; Ray, Partha Pratim; Mir, Mohammad Hedayetullah
Abstract : Two isotypical Co(ii )-based 1D coordination polymers with a linear ditopic linker along with pyridyl based ligands exhibit optoelectronic property. Abstract : Two new coordination polymers (CPs), namely [Co(adc)(4-ppy)(H2 O)2 ] n, (1 ) and [Co(adc)(4-bppy)(H2 O)2 ] n, (2 ) (H2 adc = acetylenedicarboxylic acid, 4-ppy = 4-phenylpyridine and 4-bppy = 4-(4-bromophenyl)pyridine), have been synthesized and characterized via numerous techniques including elemental analysis, infrared spectroscopy, powder X-ray diffraction (PXRD), single crystal X-ray diffraction (SCXRD), and thermogravimetric analysis (TGA). Both the compounds form one-dimensional (1D) chain-like structures constructed by linear dicarboxylate and pyridyl-based organic linkers and show significant non-covalent interactions. Both the compounds exhibit electrical conductivity and reveal Schottky barrier diode behavior. However, compound 1 shows a slightly better electrical conductivity (2.61 × 10 −5 S m −1 ) than compound 2 (2.52 × 10 −6 S m −1 ). The optical band gaps of both compounds in the solid state have also been determined via experimental measurements and compared with the theoretical values obtained from DFT calculations.